Penerapan Model Pembelajaran Radec untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Kelas IV SDN 1 Mantup - Jesica Bella Anggraini; Rizka Novi Irmaningrum; A.F. Suryaning Ati MZ (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The low reading comprehension skills of fourth grade students at SDN 1 Mantup were caused by the use of conventional teacher-centered learning methods, resulting in students being less active during the learning process. This study aimed to implement the RADEC (Read, Answer, Discuss, Explain, Create) learning model to improve the reading comprehension skills of fourth grade students at SDN 1 Mantup. This study used Classroom Action Research (CAR) conducted in two cycles. Data were collected through teacher activity observation sheets, student activity observation sheets, and reading comprehension tests.The results showed that the implementation of the RADEC learning model was able to improve the reading comprehension skills of fourth grade students at SDN 1 Mantup. This improvement could be seen from the increase in teacher activities, student activities, and students’ reading comprehension results in each cycle. Teacher activity in cycle 1 reached 51% and increased to 93% in cycle 2. Student activity in cycle 1 reached 58% and increased to 93% in cycle 2. In addition, students’ reading comprehension skills improved from 40% in cycle 1 to 86% in cycle 2. Therefore, the RADEC learning model was effective in improving the reading comprehension skills of fourth grade students at SDN 1 Mantup.